2020
DOI: 10.1186/s40001-020-00403-8
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-145 is involved in endothelial cell dysfunction and acts as a promising biomarker of acute coronary syndrome

Abstract: Background: Acute coronary syndrome (ACS) is a serious type of cardiovascular diseases. This study aimed to investigate the expression patterns and clinical value of in ACS patients, and further uncover the function of miR-145 in ACS rats. Methods:Quantitative real-time PCR was used to estimate the expression of miR-145. Diagnostic value of miR-145 was evaluated, and its correlation with endothelial injury marker (vWF and H-FABP) and pro-inflammatory cytokines (IL-6 and TNF-α) was analyzed. Coronary artery li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…A consistent finding was more recently reported also in human carotid artery stenosis [ 49 ]. Moreover, downregulation of miR-145 was also proposed as a marker of coronary event involving plaque rupture [ 50 ], reinforcing the concept that a balanced expression of this miR could be actively implicated in vascular health and stability.…”
Section: Discussionmentioning
confidence: 99%
“…A consistent finding was more recently reported also in human carotid artery stenosis [ 49 ]. Moreover, downregulation of miR-145 was also proposed as a marker of coronary event involving plaque rupture [ 50 ], reinforcing the concept that a balanced expression of this miR could be actively implicated in vascular health and stability.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-587 showed a close association with the severity of ACS patients and was considered to be a potential biomarker for the diagnosis and prognosis of ACS [ 29 ]. miR-145 was disclosed to participate in the dysfunction of endothelial cells and differentiate ACS patients from healthy controls [ 30 ]. In this study, miR-3646 was found to be upregulated in ACS patients and discriminate ACS patients from healthy volunteers and non-ACS patients with high sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Wu and colleagues [ 33 ] revealed the function of miR-145 in regulating vascular endothelial cells and inflammation response by targeting the same FOXO1 gene. The miR-145 expression was found to be low in patients with ACS and negatively correlated with endothelial injury biomarkers and pro-inflammatory cytokines.…”
Section: Current Outlooks For Mirnas In Ischemic Heart Diseasementioning
confidence: 99%